Un Modelo CcP Del Mercado De Valores; A CasP Model of the Stock Market - Shimshon Bichler; Jonathan Nitzan (Revista de Economía Institucional, 2017)
SPANISH ABSTRACT: La mayoría de las explicaciones de las alzas y bajas del mercado de valores se basan en la comparación de la lógica “fundamental” subyacente de la economía con los factores exógenos que supuestamente la distorsionan. Este artículo presenta un modelo radicalmente distinto, y examina el mercado de valores desde la perspectiva del poder capitalizado y no desde el punto de vista de una economía distorsionada. El modelo demuestra que la valoración de acciones representa poder capitalizado, que el poder capitalizado está entrelazado al temor sistémico, y que estos dos elementos son mediados por el sabotaje estratégico. Este modelo triangular ofrece una base para examinar los límites del poder capitalizado y su relación con la transformación histórica y actual del modo de poder capitalista. – – ENGLISH ABSTRACT: Most explanations of stock market booms and busts are based on contrasting the underlying `fundamental' logic of the economy with the exogenous, non-economic factors that presumably distort it. Our paper offers a radically different model, examining the stock market not from the mechanical viewpoint of a distorted economy, but from the dialectical perspective of capitalized power. The model demonstrates that (1) the valuation of equities represents capitalized power; (2) capitalized power is dialectically intertwined with systemic fear; and (3) systemic fear and capitalized power are mediated through strategic sabotage. This triangular model, we posit, can offer a basis for examining the asymptotes, or limits, of capitalized power and the ways in which these asymptotes relate to the historical and ongoing transformation of the capitalist mode of power.
Additional information: Translated from the English by Alberto Supelano.
Keywords: 330; capital as power; crisis; mismatch thesis; stock market; strategic sabotage; systemic fear; valuation